Dental prophylaxis decreases the risk of esophageal cancer in males; a nationwide population-based study in Taiwan. - Ya-Ling Lee (Public Library of Science (PLoS), 2014)
Background Periodontal disease (PD) is one of the most common chronic inflammatory diseases. Esophageal cancer (EC) is also a common cause of death due to cancer among males. Systemic inflammatory processes have been shown to increase the risk of cancer. We conducted a retrospective cohort study to investigate the association between PD and EC. Methods A total of 718,409 subjects were recruited from the Taiwan National Health Insurance Research Database (NHIRD) and followed from January 1, 2000 to December 31, 2010. Of these, 519,831 subjects were diagnosed with PD and were grouped according to the most advanced treatment they received: dental prophylaxis, intensive treatment, or no treatment. The IRs of EC were compared among groups. Results A total of 682 patients developed EC, resulting in an overall IR of 0.11 case-number per 1000 person-years (‰/y). The dental prophylaxis group had a significantly lower IR of EC (0.06‰/y) than other groups (p<0.001). Multivariable Cox regression analysis further revealed that male subjects [hazard ratio (HR) = 10.04, 95% confidence interval (CI)  = 7.58-13.30], as well as a history of esophageal ulcers (HR = 7.10, 95% CI = 5.03-10.01), alcohol abuse (HR = 5.46, 95% CI = 2.26-13.18), or esophageal reflux (HR = 1.86, 95% CI = 1.02-3.52), were factors associated with a higher risk of EC. And the dental prophylaxis group showed a significantly lower risk for EC (HR = 0.53, 95% CI = 0.44-0.65). Further subgroup analysis showed that the dental prophylaxis group among males had a significant lower risk (HR = 0.54, 95% CI = 0.44-0.66) for EC, while that of the females did not has statistically significant difference. Conclusion For this cohort, subjects received dental prophylaxis reduced the risk of EC compared to all PD and no PD groups among males.